Return to sport after hallux valgus surgery in athletes: Current Evidence - López, Mario; Wagner, Emilio (Journal of the Foot & Ankle, 2025)
Abstract Introduction: Hallux valgus affects approximately one-third of the population and is characterized by a three-dimensional deformity. This condition can impact performance in sport-related activities. The most suitable surgical option for athletes with hallux valgus remains unclear. The current lack of evidence and studies covering various registration systems and sports makes them non comparable. Objective: This study aims to present evidence regarding the different surgical techniques for hallux valgus and their impact on return to sports. Methods: Two authors conducted a search using PubMed, Embase, MEDLINE, Google Scholar. The inclusion criteria were articles involving case series published in the English language from 1995 through January 2025. Exclusion criteria were hallux rigidus, traumatic deformity, sesamoid pathology, and review articles. Studies that did not describe the athlete’s level of play and the type of sport were also excluded. Results: This review identified eight studies on the surgical correction of hallux valgus in “athletes” published to date. Currently, the evidence supports Chevron osteotomy for mild to moderate deformities and Scarf osteotomy for moderate to severe deformities, both resulting in low recovery time. At best, metatarsophalangeal arthrodesis provides 96% satisfaction in sport-related activities. Conclusion: Chevron and scarf osteotomies are effective surgeries for athletes with minor deformities. For severe hallux valgus, there is no clear consensus, but metatarsophalangeal arthrodesis appears to demonstrate a good result. Future studies need to document activity levels and return to sport to help guide treatment. Level of evidence I; Systematic Review.